2001
DOI: 10.1002/1522-2683(200108)22:14<3026::aid-elps3026>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of apoptosis initiation induced byall-trans retinoic acid in human acute promyelocytic leukemia cells

Abstract: The irreversible destiny of apoptosis in its early stage might play a critical role in the apoptosis of human acute promyelocytic leukemia (APL) cell line induced by all-trans retinoic acid (ATRA). To characterize protein alterations during the apoptosis-initiation phase and to understand the metabolic status at that time, we investigated the protein profiles in the apoptosis-initiation phase of APL cell line HL-60 by proteomic analysis. ATRA-withdrawal was conducted to demonstrate that there was committed ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…The interest and importance of proteomics in the research of prognostic markers was revealed for AML, 13,14 clinical behavior predictions in adult acute lymphoblastic leukemia 15 and therapy-related proteome variations. 16 Finally, functional proteomic profiling confirmed that specific protein expression patterns correlate with outcome and prognosis, thus providing new molecular classifications useful for predicting the risk of AML patients at diagnosis. 17 In this context, we developed a surface-enhanced laser desorption/ionization time-of-flight (SELDI-TOF)-based protein profile of leukemic cells associated with tandem MS (MALDI-TOF/TOF and nanoLC MS/MS) to identify new, specific biomarkers of high-risk AML that are present at the time of diagnosis.…”
Section: Introductionmentioning
confidence: 84%
“…The interest and importance of proteomics in the research of prognostic markers was revealed for AML, 13,14 clinical behavior predictions in adult acute lymphoblastic leukemia 15 and therapy-related proteome variations. 16 Finally, functional proteomic profiling confirmed that specific protein expression patterns correlate with outcome and prognosis, thus providing new molecular classifications useful for predicting the risk of AML patients at diagnosis. 17 In this context, we developed a surface-enhanced laser desorption/ionization time-of-flight (SELDI-TOF)-based protein profile of leukemic cells associated with tandem MS (MALDI-TOF/TOF and nanoLC MS/MS) to identify new, specific biomarkers of high-risk AML that are present at the time of diagnosis.…”
Section: Introductionmentioning
confidence: 84%
“…The results presented here show that the level of RhoGDI in cancer cells regulates the apoptotic response of the cells to these two chemotherapy agents as well as to staurosporine and suggest that RhoGDI overexpression gives cancer cells a survival mechanism against these antitumor chemotherapies. Consistent with this hypothesis, treatment of myeloid leukemia cells with agents that increase cell death in response to chemotherapy drugs (all-trans retinoic acid and the cyclin-dependent kinase inhibitor bohemine treatment) was associated with down-regulation of RhoGDI levels (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts at the proteomic characterization of leukemic cells have mainly used matrix-assisted laser desorption/ionization-time of flight analysis after two-dimensional gel electrophoresis. The available evidence is sparse but supports the importance of proteomic analysis of leukemias, e.g., for class distinction (4), target identification (5), apoptosis initiation (6), and stem cell analysis (7). However, the proteins isolated by these technologies need to be identified and characterized by other means, and a more comprehensive profiling could not be achieved due to the excessive requirements for material to study and for the time required to perform each analysis.…”
Section: Introductionmentioning
confidence: 99%